A comparison of long‐term clinical outcomes between percutaneous coronary intervention (PCI) and medical therapy in patients with chronic total occlusion in noninfarct‐related artery after PCI of acute myocardial infarction. Issue 1 (6th January 2022) - Qin, Qing; Chen, Lu; Ge, Lei; Qian, Juying; Ma, Jianying; Ge, Junbo
Abstract: Background: Chronic total occlusion (CTO) in a noninfarct‐related artery (IRA) is one of the risk factors for mortality after acute myocardial infarction (AMI). However, there are limited data comparing the long‐term outcomes of patients undergoing percutaneous coronary intervention (PCI) with patients having medical therapy (MT) in CTO lesion after AMI PCI. Methods: We retrospectively enrolled 330 patients (successful CTO PCI in 166 patients, failed CTO PCI in 32 patients, MT in 132 patients) with non‐IRA CTO from a total of 4372 patients who underwent PCI after AMI in our center. Propensity score matching (PSM) was used to adjust for baseline differences. Results: The primary analysis is based on the intention‐to‐treat population. During a median follow‐up period of 946 days, patients in the PCI group ( n  = 198) had significantly higher cardiac death‐free survival (96.6% vs. 82.8%, p  = .004) compared with patients in MT group ( n  = 132). However, no significant difference in the occurrence of cardiac death was observed after PSM. The analysis based on the per‐protocol population demonstrated significantly higher cardiac death‐free survival in the successful CTO PCI group ( n  = 166) compared with the occluded CTO group ( n  = 164) both before and after PSM. In subgroup analysis, successful CTO PCI was associated with less cardiac death in patients over 65 years old, with LVEF < 50%, left anterior descending (LAD) IRA, and non‐LAD CTO lesion compared with occluded CTO group. Conclusions: Patients undergoing successful revascularization of non‐IRA CTO after AMI might have a better long‐term prognosis. Moreover, patients with LVEF < 50% may benefit from successful non‐IRA CTO PCI after AMI.